Level of Psycoeducation Effectiveness on Adaptation Fracture Patients at Pirngadi Hospital Medan City - Rina Rahmadani Sidabutar; Budiana Yazid; Heni Triana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Two thirds of injury cases in developing countries, including Indonesia, are still a major public health problem in all countries. In 2020 there were 152.256 injury cases in Indonesia (17.8%). Fractures cause a variety of negative effects, including psychological, social, and spiritual. A report from the Department of Health shows that 15 percent of fracture sufferers experience emotional stress and even depression. Psychological education helps in the treatment and reduction of depressive symptoms, which are part of the psychological response to disability. This research is to find out how well psychoeducation helps fracture patients adapt at Pirngadi Hospital, Medan City. This type of research is quasi-experimental with a pre-test-post-test design with control group. This research was carried out at Pirngadi Hospital, Medan City from 21 July to 23 August 2023. The study population included 67 patients who experienced grade 2 and 3 fractures. The sampling technique is non-probability sampling. The number of samples in this study was 16 people for the control group and 16 people for the treatment group. The research instrument has been tested for validity and reliability. Univariate analysis to describe research variables, while bivariate analysis with dependent t test to determine the mean differences in the treatment group before and after being given psychoeducation and in the control group at pre-test and post-test. The results of the study showed that there was a difference in the average adaptation of fracture patients who were given psychoeducational intervention compared to the group of patients who were not given intervention with p value = 0.000; 95% CI < alpha = 0.05. Keywords: Frakture, Injury Patient, Psychoeducation